A cross-correction gene therapy approach for CDKL5 deficiency disorder improves the pathological phenotype of CDD patient-derived cortical organoids - Medici, Giorgio; Bove, Angelica M.; Trazzi, Stefania; Puppo, Francesca; Loi, Manuela; Mottolese, Nicola; Candini, Giulia; Trebbi, Federica; Sanchez, Sandra; Muotri, Alysson R.; Ciani, Elisabetta (Frontiers in Bioengineering and Biotechnology, 2026)
Efficient delivery of biological material to the central nervous system remains a key limitation of conventional gene therapies. Recently, we developed a novel strategy based on a secretable and cell-penetrating TATk-CDKL5 fused protein which enhances the brain biodistribution and the therapeutic efficiency of the gene therapy approach in a mouse model of CDKL5 Deficiency Disorder (CDD). Here, to compare the efficacy of the TATk-CDKL5 gene therapy with a conventional approach in correcting the CDKL5 Deficiency Disorder pathological phenotype, we employed cortical organoids generated from CDD patient-derived iPSCs as a human model of CDD. We found greater therapeutic efficacy of the recombinant TATk-CDKL5 protein compared to the CDKL5 protein alone in improving or ameliorating defects caused by the absence of CDKL5, such as abnormal hyperexcitability evaluated with microelectrode arrays (MEA). Interestingly, CDD cortical organoids exhibited reduced cell proliferation and increased neuronal cell death compared to control cortical organoids; defects that were only restored by the expression of the recombinant TATk-CDKL5 protein. Based on the results from phenotypic and functional readouts, these findings suggest that gene therapy using a cross-correction approach offers superior efficiency in treating CDD.